Modulation of the electromagnetic shielding effectiveness through micro/macrostructure design for electronic packaging - Lizhi Guan; Jingbo Fan; Zhi Kai Ng; Edwin Hang Tong Teo; Hortense Le Ferrand (NPG Asia Materials, 2024)
Abstract Lightweight electronic packaging that provides mechanical protection, cooling ability, and customizable electromagnetic interference (EMI) shielding effectiveness (SE) is needed for next-generation electronics. Although electronic packaging solutions with excellent EMI SE exist, there is limited research on how hierarchical design can modulate the EMI SE of an electronic packaging material on demand. In this study, the deliberate precise micro/macrostructure design of graphite-based materials using magnetically assisted 3D printing allows tuning of the EMI SE in the X band (8–12 GHz), leading to a maximum total shielding performance of 90 dB. Aligning high-density graphite microplatelets during 3D printing also remarkably amplified the total SE by 200%. Subsequently, rationally designing the oriented microstructure within a geometrical shape increases the reflection and improves the EMI SE from 40 to 60 dB in a specific direction. Our proof-of-concept samples demonstrate the potential of precise micro/macrostructure design for customizing and enhancing electronic packaging’s EMI SE while achieving good heat dissipation and mechanical protection using a versatile 3D printing method. These advances pave the way for more reliable and safer electronic systems.